Tales from a not-so-talented pop star - Russell, Rachel Renee (New York : Aladdin, 2011)
When scholarship student Nikki Maxwell, whose father is the school exterminator, decides to enter the talent show at her expensive private school, her nemesis MacKenzie threatens to reveal Nikki's status to the rest of the school.
5.2
3-6
770
W
Keywords: Talent shows -- Juvenile fiction; Friendship -- Juvenile fiction; Popularity -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Talent shows -- Fiction; Friendship -- Fiction; Popularity -- Fiction; Middle schools -- Fiction; Diaries -- Fiction; Schools -- Fiction; Talent shows -- Fiction; Friendship -- Fiction; Popularity -- Fiction; Middle schools -- Fiction; School stories; Talent shows -- Fiction; Friendship -- Fiction; Popularity -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Diaries -- Fiction; Diary fiction